Sistem Informasi Monitoring Pembangunan pada PT. Rahayu Lestari Sejahtera - Muhammad Hanan Majid; Agustinus Budi Santoso; Edy Siswanto (STMIK Banjarbaru, 2026)
The monitoring process of housing construction progress at PT Rahayu Lestari Sejahtera was still carried out through separate communication channels, causing report data to be scattered, recapitulation to take longer, and project progress to be unavailable in real time. This research aimed to build a web-based information system to support centralized reporting, verification, and presentation of construction progress data. The research applied a Research and Development (R&D) approach, while the system development process used Agile Development with a Kanban approach. The application was built using Laravel, Filament, and MySQL, and was equipped with Role-Based Access Control to differentiate access rights for foremen, construction staff, and management. The novelty of the system was the verification of reports by construction staff before information was presented to management, and progress calculation using weighted checklists. User Acceptance Testing produced a feasibility score of 80%, categorized as feasible.Keywords: Progress Monitoring; Information System; Laravel; Kanban; User Acceptance Testing Abstrak Proses pemantauan progres pembangunan perumahan di PT Rahayu Lestari Sejahtera masih berjalan melalui media komunikasi yang terpisah, sehingga data laporan tersebar, rekapitulasi membutuhkan waktu lebih lama, dan perkembangan proyek belum dapat dipantau secara real-time. Penelitian ini bertujuan membangun sistem informasi berbasis web untuk mendukung pelaporan, verifikasi, dan penyajian data progres pembangunan secara terpusat. Metode penelitian yang digunakan adalah Research and Development (R&D), sedangkan proses pengembangan sistem menerapkan Agile Development dengan pendekatan Kanban. Aplikasi dibangun menggunakan Laravel, Filament, dan MySQL, serta dilengkapi Role-Based Access Control untuk membedakan hak akses mandor, staf konstruksi, dan pimpinan. Kebaruan sistem terdapat pada proses verifikasi laporan oleh staf konstruksi sebelum informasi disajikan kepada pimpinan, serta perhitungan progres menggunakan checklist berbobot. Hasil User Acceptance Testing memperoleh nilai kelayakan 80% dengan kategori layak.